The importance of having a partner: male help releases females from time limitation during incubation in birds - Matysioková, Beata; Remeš, Vladimír (Frontiers in zoology, 2014)
INTRODUCTION: Male contribution to parental care varies widely among avian species. Yet the reasons for this variation, as well as its consequences, are still unclear. Because the amount of care provided by one sex is ultimately constrained by the time available for energy acquisition, contribution by the other sex should increase when overall parental workload is high. We tested this prediction by analyzing male contribution to incubation in 528 populations of 320 species of passerines, where females usually devote more time to incubation than males. Our worldwide sample included species with female-only parental care (the male is not present), incubation feeding (the male feeds the incubating female), and shared incubation (both sexes incubate the eggs). RESULTS: Overall nest attentiveness was greatest in species with shared incubation followed by species with incubation feeding and lowest in species with female-only care. Nest attentiveness and the degree of male contribution to incubation in species with shared incubation were very strongly correlated, whereas this correlation was absent in females. Interestingly, female contribution decreased towards the equator while male contribution did not change significantly with latitude. Hence, relative male incubation effort increased towards the equator, whereas that of female decreased. In species with incubation feeding, female nest attentiveness increased with the frequency of male feeding. CONCLUSIONS: These findings support the hypothesis that male help is indispensable for increasing nest attentiveness in birds, either in the form of incubation feeding (supply of energy) or direct incubation of eggs. We conclude that energy acquisition constraints might be a potent force driving sex-specific contribution to parental care.